Human rights - Tomuschat, Christian (Oxford University Press, 2003)
This volume presents human rights in action, focussing on their effectiveness as legal tools designed to benefit human beings. By combining conceptual analysis with an emphasis on procedures and mechanisms of implementation, it provides a multidimensional overview of human rights. Beginning with an analysis of the historical and conceptual foundations of human rights, the volume then focusses upon the different mechanisms which may be employed in translating human rights from a promise into a reality. Special emphasis is placed upon the United Nations procedures available to achieve this end